2009
DOI: 10.1186/1758-2652-12-7
|View full text |Cite
|
Sign up to set email alerts
|

The cost and impact of male circumcision on HIV/AIDS in Botswana

Abstract: The HIV/AIDS epidemic continues to be a major issue facing Botswana, with overall adult HIV prevalence estimated to be 25.7 percent in 2007. This paper estimates the cost and impact of the draft Ministry of Health male circumcision strategy using the UNAIDS/WHO Decision-Makers' Programme Planning Tool (DMPPT). Demographic data and HIV prevalence estimates from the recent National AIDS Coordinating Agency estimations are used as input to the DMPPT to estimate the impact of scaling-up male circumcision on the HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 14 publications
2
39
0
Order By: Relevance
“…Several modeling studies found that the longterm population-level impact of widespread implementation and scale-up of voluntary medical male circumcision (VMMC) services will result in substantial reductions in HIV incidence for both men and women [8][9][10][11][12]. As a result, ten of the fourteen high-priority countries are actively engaged in national VMMC program scale-up [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several modeling studies found that the longterm population-level impact of widespread implementation and scale-up of voluntary medical male circumcision (VMMC) services will result in substantial reductions in HIV incidence for both men and women [8][9][10][11][12]. As a result, ten of the fourteen high-priority countries are actively engaged in national VMMC program scale-up [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that adult male circumcision (AMC) can be a cost-effective strategy for prevention of heterosexual acquisition of HIV in men. Several economic evaluations [11][12][13][14][15] have shown that AMC is cost effective, or even cost saving (a cost-saving intervention is one that actually saves society money in the long run by preventing costly medical care) for the prevention of heterosexual acquisition of HIV in men. A preliminary examination of the existing economic evaluations suggests that, studies have tended to focus on population in a limited geographic area, have expressed results in terms of cost per HIV infection averted (HIA), or have not considered DALYs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since long, phimosis has been considered as a predisposing factor for penile and cervical cancer and circumcision has been shown to reduce the incidence. In the HIV prevalent areas, circumcision has been advocated to decrease transmission of the disease [9]. Transmission of other sexually transmitted diseases has also been shown to reduce by routine circumcision.…”
mentioning
confidence: 99%